Relationship between Quality of Life, Depression, and Participation in Elderly Integrated Health Service Post among Older Adults - Margaretha, Christine; Sarjana, Widodo; Suharto, Suharto; Jusup, Innawati (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Older adults are susceptible to worsened quality of life (QOL) and depression due to aging. Elderly integrated health service post (EIHSP) is community-based health care that aims to improve older adults’ health; however, not all older adults participate in this health service.Purpose: This study was conducted to assess the relationship between the QOL, depression level, and older adults’ participation in EIHSP.Methods: A cross-sectional study was carried out among 102 older adults in a community-dwelling area in Semarang, Indonesia. Respondents were recruited using a total sampling technique. QOL was assessed by the WHOQOL-BREF questionnaire, while the level of depression was assessed by Geriatric Depression Scale (GDS) questionnaires. Descriptive statistics, Spearman, and Sommers’ d tests were used to analyze the data.Results: Higher participation in EIHSP significantly affected QOL on every domain (general quality of life, physical, psychological, social relationship, and environmental domains) with p<0.05. This study also showed that participation in EIHSP had a significant relationship with depression levels (p=0.002). Furthermore, higher depression levels significantly affected QOL on every domain (p<0.05).Conclusion: This study showed that older adults’ participation in EIHSP had a significant relationship with QOL and depression. Community nurses can promote the utilization of EIHSP among older adults for better physical and mental health. Future studies should investigate these relationships in a larger sample size.